Victorian Drug Strategy Household Survey, 1995 - Bland, Luz (ADA Dataverse, 2019)
This study is the second in a series of Victoria-specific surveys undertaken in conjuction with the National Drug Strategy. The primary objectives of the study were to obtain a) an update on data related to community attitudes, behaviour and knowledge of drugs and b) information on both emerging drug issues and what Victorians see as priorities for government action. The information collected in the survey is to be used to improve the effectiveness of and accessibility to alcohol and drug related programs, the effectiveness and acceptability of supply control and regulatory measures, and the tailoring of harm reduction measures to current community attitude and practices. The main variables include: the extent of drug experimentation and use in the population; the impact of drug use; patterns of drug use, including the extent of co-use of marijuana and alcohol with other drugs; venues in which marijuana and alcohol are used; current attitudes towards drug use; the extent and reporting of alcohol-related crime and violence; the perceived role of schools in drug education; concerns held by parents of school age children; sources of information about drugs; possible actions to limit public drunkenness; location of alcohol-related crime or violence; other consequences of alcohol use (e.g. sexual harassment and the need to take care of others); alcohol consumption during working hours; the use of services in relation to drug problems for self and for others; consumption of home-brewed alcohol, and home production of alcohol and marijuana; most frequent purchase places for alcohol and tobacco; reactions to proposals about testing drivers for drugs other than alcohol; reactions to proposals concerning later night trading for pubs and clubs; and knowledge of the health risks involved with tobacco, alcohol, and marijuana. Demographic variables include age, sex, location, employment status, marital status, children, income, country of birth and highest education level.